COMPUTER ANALYSIS OF DATA ON GENE EXPRESSION IN BRAIN CELLS OBTAINED BY MICROARRAY TESTS AND HIGH-THROUGHPUT SEQUENCING - I. V. Medvedeva; O. V. Vishnevsky; N. S. Safronova; O. S. Kozhevnikova; M. A. Genaev; A. V. Kochetov; D. A. Afonnikov; Y. L. Orlov (Вавиловский журнал генетики и селекции)
The scope of neurobiological studies has been greatly expanded in the last years. It is accompanied by accumulation of a huge body of experimental data on the structure, function and evolution of the nervous system at different hierarchical levels of its organization. High-throughput sequencing technologies and microarray tests permit the expression of thousands of genes to be analyzed with regard to cell location in the brain. Methods of gene expression analysis are briefly reviewed in the context of brain research. We have analyzed specific features of genes differentially expressed in brain cells. Some genes overexpressed in brain tissues are associated with neurological diseases. The numbers of exons and active transcripts in genes differentially expressed in different organs are considered. Statistically significant difference in such parameters is shown for genes intensely expressed in the brain and other organs. Examples of such differentially expressed genes associated with neurological deceases are presented.